A comparison of deviations from balanced and negative time perspectives between elite and non-elite wrestlers - Nazarpouri, S. (Sport Psychology Studies, 2025)
Time perspective, as measured by the Zimbardo Time Perspective Inventory (ZTPI), has been recognized as an important psychological factor in domains such as education, health, and, to a lesser extent, athletic performance. However, ZTPI scores have been operationalized in various ways, including composite scores that simultaneously consider the mean values of its five dimensions. The present study examined differences in two composite indices Deviation from a Balanced Time Perspective (DBTP) and Deviation from a Negative Time Perspective (DNTP) among elite and non-elite Iranian wrestlers. This comparative study included 202 male wrestlers (86 elites with national team experience and 116 non-elites active at club or provincial levels) selected via purposive sampling. The ZTPI questionnaire and relevant computational formulas were employed to extract DBTP and DNTP indices. Data were analyzed using multivariate analysis of variance (MANOVA) in SPSS version 26, with a significance level of a = 0.05. Results indicated that elite wrestlers exhibited significantly lower deviation from a balanced time perspective (p0.001, n²=.744) and lower tendencies toward negative dimensions (p<0.001, n²=.880) such as Past Negative and Fatalistic Present compared to their non-elite counterparts. These findings underscore the importance of a BTP profile as a key psychological characteristic associated with successful athletic performance in wrestling. Based on these results, future studies should further explore DBTP and DNTP indices in athletes across various sports, cultures, and age groups to enhance the generalizability of findings.